Working Conditions and Employees’ Productivity in Cross River State Civil Service, Nigeria - Ipole Peter A.; Okpa John T. (European Scientific Journal, ESJ, 2019)
This study examined the relationship between working conditions and employees’ productivity in Cross River State Civil Service, Nigeria. The study specifically examined the relationship between reward system, promotions, and employees’ productivity. The research adopted a descriptive survey design. The instrument used for data collection was a questionnaire distributed to nine hundred and twelve (912) staff of Cross River State Civil Service. Data were statistically tested using linear regression statistical technique method. The results show that there is a significant relationship between reward system, promotions, and employees’ productivity.